2012
DOI: 10.1080/17518253.2011.578079
|View full text |Cite
|
Sign up to set email alerts
|

Formylation and acetylation of alcohols using Amberlyst-15®as a recyclable heterogeneous catalyst

Abstract: Formylation of alcohols with ethyl formate in the presence of solid acidic resin Amberlyst-15 as a catalyst was carried out. Good to excellent yields of products were obtained. The catalyst also works for the acetylation of alcohols with ethyl acetate at reflux temperature. Simple work-up, reusability, nontoxicity, and stability of the catalyst are the advantages of this work as compared to conventional protocols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, transesterification using ethyl acetate (EtOAc) has attracted much attention in recent years, since the reaction can be environmentally friendly, ideally producing only ethanol as a byproduct. Therefore, many useful transesterification reactions of alcohols with ethyl acetate using LiAl(O n C 8 H 17 ) alumina, metallic sulfates, PPh 3 /CBr 4 , Ce(OTf) 4 , distannoxane, In/I 2 , K 5 CoW 12 O 40 ⋅3H 2 O, N ‐hetrocyclic carbene, silphos, H 3 PW 12 O 40 , Zn 4 (OCOCF 3 ) 6 O, amberlyst‐15, silica‐bonded N ‐propyl sulfamic acid, lanthanum(III) catalyst, NaO t Bu, KO t Bu, I 2 , and enzymes have been reported. However, since most of these reactions require heating or strong bases (Scheme (a)), the development of a reaction that proceeds under mild conditions (Scheme (b)) is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, transesterification using ethyl acetate (EtOAc) has attracted much attention in recent years, since the reaction can be environmentally friendly, ideally producing only ethanol as a byproduct. Therefore, many useful transesterification reactions of alcohols with ethyl acetate using LiAl(O n C 8 H 17 ) alumina, metallic sulfates, PPh 3 /CBr 4 , Ce(OTf) 4 , distannoxane, In/I 2 , K 5 CoW 12 O 40 ⋅3H 2 O, N ‐hetrocyclic carbene, silphos, H 3 PW 12 O 40 , Zn 4 (OCOCF 3 ) 6 O, amberlyst‐15, silica‐bonded N ‐propyl sulfamic acid, lanthanum(III) catalyst, NaO t Bu, KO t Bu, I 2 , and enzymes have been reported. However, since most of these reactions require heating or strong bases (Scheme (a)), the development of a reaction that proceeds under mild conditions (Scheme (b)) is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Yamamoto and Ishihara et al reported highly efficient and direct ester condensation in hydrocarbons by using hafnium(IV) salts such as an HfCl 4 ·(THF) 2 catalyst under azeotropic reflux conditions. Transesterification of various esters with alcohols using heterogeneous and homogeneous acidic catalysts has also been reported 28 29 30 31 32 33 34 35 36 37 38 .…”
mentioning
confidence: 96%